2017
DOI: 10.1111/bcp.13226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type 2 diabetes mellitus on the pharmacokinetics and transplacental transfer of nifedipine in hypertensive pregnant women

Abstract: There was no influence of T2DM on the pharmacokinetics or placental transfer of nifedipine in hypertensive women with controlled diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 48 publications
(45 reference statements)
2
23
1
1
Order By: Relevance
“…Similarly, pregnant women with gestational diabetes showed significantly higher C max and AUC of lidocaine following peridural anesthesia administration of lidocaine than non-diabetic patients [61]. However, oral plasma concentrations of nifedipine [62] and metoprolol [63] in pregnant women with gestational diabetes were comparable to those in non-diabetic pregnant women. Adith et al [64] investigated phenytoin kinetics in 10 male type 1 and 10 type 2 diabetic patients.…”
Section: Cyp450smentioning
confidence: 90%
“…Similarly, pregnant women with gestational diabetes showed significantly higher C max and AUC of lidocaine following peridural anesthesia administration of lidocaine than non-diabetic patients [61]. However, oral plasma concentrations of nifedipine [62] and metoprolol [63] in pregnant women with gestational diabetes were comparable to those in non-diabetic pregnant women. Adith et al [64] investigated phenytoin kinetics in 10 male type 1 and 10 type 2 diabetic patients.…”
Section: Cyp450smentioning
confidence: 90%
“…During the past several years, intense investigative and clinical efforts have focused on the impact of drug‐altered pharmacokinetics in diabetes [9]. Diabetes mellitus can alter the kinetic disposition and the metabolism of drugs on the investigated drug, and on its metabolic and excretion pathways [10–12]. Recently, some papers reported that the pharmacokinetics of clinical drugs is altered in individuals with diabetes mellitus, including gentamicin [13], metoprolol [14], berberine [15], baicalin [16], catalpol [17], and geniposide [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some papers reported that the pharmacokinetics of clinical drugs is altered in individuals with diabetes mellitus, including gentamicin [13], metoprolol [14], berberine [15], baicalin [16], catalpol [17], and geniposide [18]. Specifically, type 2 diabetes mellitus alters the pharmacokinetic (PK) features of some drugs such as amlodipine, nisoldipine, and nifedipine [9, 12, 19]. The curative effects of some TCMs can be reflected when the body is in a specific pathological state.…”
Section: Introductionmentioning
confidence: 99%
“…Nifedipine, a dihydropyridin calcium channel, is mostly utilized for the clinical treatment of precordial angina, hypertension, and other vascular diseases (Yasam et al., 2016 ; Rubini et al., 2017 ). Importantly, nifedipine is a nonpolar drug that is completely absorbed by the gastrointestinal tract (Grigoriev et al., 2016 ; Filgueira et al., 2017 ). Its metabolism may be affected by microbiota in the stomach and intestine although the biotransformation of nifedipine by enteric microorganism has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%